Impact of standardised documentation on post take ward round. (24th May 2012) - Newnham, A; Hine, C; Agwu, JC
Abstract : Aims: Does the acronym "Please Verify Info For Doctors and Please Note Every Plan" (Problems, Vital signs, Investigations, Fluids, Drugs and Patient/Parent concerns, Nursing concerns, Examination, Plan) improve documentation on the post take ward round (PTWR). Does improved documentation affect re-admission rate and length of stay? Methods: 50 consecutive notes for all children admitted under a single Consultant Paediatrician from June-September 2010 (pre-acronym) were compared to 50 consecutive notes for children admitted June-September 2011 (post-acronym). The adequacy of documentation on the PTWR including patient demographics was compared between the two cohorts. As a secondary outcome we evaluated whether the length of hospital stay and readmission (within 28 days) varied between the two cohorts. Significance values were calculated using Fisher's exact test and paired T-Test. Results: The documentation of problem, investigations, fluids, drugs, patient/parental concerns and nursing concerns all showed significant improvement in recorded documentation after the introduction of the PTWR acronym (table 1 ). There was no significant change in documentation of vital signs, examination and plan; although these variables all had high documentary compliance prior to the introduction of the acronym. There was no significant difference between length of stay (p=0.8934) or re-admission rates (p=0.2044) between the two cohorts. The patient demographics did not differ significantly between the two cohorts. Conclusion: The use of a PTWR acronym significantly improves documentation. This is important as the PTWR is the key forum for exchange of information between doctor, nurse and patient. As the PTWR often defines the focus of management it is essential that we strive to incorporate methods to improve its documentation and hence implementation.